The Diversity of Functions and Structures of Research and Development Organizations - An Indispensable Trend of the Autonomous Institution in Science - Ngoc, Pham Thi Bich (VNU Journal of Science: Policy and Management Studies; Vol 34 No 1DO - 10.25073/2588-1116/vnupam.4129, 2018)
Abstract: In the former centralized command economy, Vietnam’s R&D institutes were mechanically designed with simple functional models and simple organizational structures. During the transition to the market economy, this model became inadaptable to the rapidly changing environment. Therefore, the R&D institutes had to adjust themselves to a more flexible functional model with structural diversification. This has also been the inevitable trend of the autonomous institution in science. Keywords: Diversification of functions and structures